2018
DOI: 10.1016/j.rpor.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

11C-methionine positron emission tomography for target delineation of recurrent glioblastoma in re-irradiation planning

Abstract: A margin of at least 5 mm around the high intensity area on T2-MRI is necessary in the target volume delineation of recurrent glioblastoma for the coverage of MET-PET findings in re-radiation therapy planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The standard first-line treatment for glioblastoma involves a variety of modalities, including surgical resection, radiotherapy and temozolomide-adjuvant chemotherapy (6). Despite surgical resection and chemoradiation, tumors in almost all patients are likely to relapse, with a 2-year survival rate of only 26% following relapse (7). There is currently no standard and uniform management method for recurrent glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…The standard first-line treatment for glioblastoma involves a variety of modalities, including surgical resection, radiotherapy and temozolomide-adjuvant chemotherapy (6). Despite surgical resection and chemoradiation, tumors in almost all patients are likely to relapse, with a 2-year survival rate of only 26% following relapse (7). There is currently no standard and uniform management method for recurrent glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…11 C-MET also has utility in evaluating glioma patients who undergo other forms of treatment. A study found that 11 C-MET was useful in monitoring the short-term therapeutic effects of laser-induced interstitial thermotherapy (LITT) in the management of GBM patients, as a continuous decline in metabolic tumor volume indicated by 11 C-MET correlated with treatment [27]. Regarding treatment planning, this radiotracer has been used to delineate tumor extent for re-irradiation, showing uptake outside the CE-MRI enhancement region in 74% of patients [28].…”
Section: C-metmentioning
confidence: 99%
“…Positron emission tomography (PET) has been used in the evaluation of brain tumors for many years (4), showing utility in several instances such as improving delineation of tumor boundaries for surgery and radiotherapy planning (5), differentiating between tumor progression and treatment-related changes (6), monitoring early/late therapy response (7), and identification of favorable biopsy sites (8). Historically, evaluation of glucose metabolic rate ( 18 F-FDG) has been used in assessing brain tumors, with sensitivity being hindered by elevated normal background uptake of 18 F-FDG, as well as increased glucose usage due to inflammatory responses potentially independent to the tumor response or growth.…”
Section: Introductionmentioning
confidence: 99%